Clinical and pathologic characteristics of pauci-immune anti-myeloperoxidase antibody associated glomerulonephritis with nephrotic range proteinuria - Peng-Cheng Xu; Tong Chen; Shan Gao; Shui-Yi Hu; Li Wei; Tie-Kun Yan (Renal Failure, 2018)
Background: Heavy proteinuria in antineutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis (GN) is usually considered to be associated with immune deposits in renal biopsy. Nephrotic ANCA GN without immune deposits (pauci-immune) is rare and has not been studied specially. In this study characteristics of these patients are to be investigated. Methods: Clinical and pathological characteristics from 20 kidney biopsy-proven pauci-immune anti-myeloperoxidase antibody-associated GN patients with nephrotic proteinuria were analyzed and were compared with ANCA GN patients without nephrotic proteinuria. Results: Acute kidney injury (AKI) and gross hematuria were much prevalent but extra-renal involvement was less prevalent in pauci-immune ANCA GN with nephrotic proteinuria than in pauci-immune ANCA GN without nephrotic proteinuria. No more severe hypoalbuminemia, hypercoagulability, hyperlipidemia or higher thrombosis incidence were found between two groups. Compared with patients without nephrotic proteinuria, patients with nephrotic proteinuria had more prevalent crescentic category in histopathology. Proteinuria decreased quickly after treatment but much poorer renal prognosis was found in pauci-immune ANCA GN with nephrotic proteinuria. The results of urinary albumin to total protein ratio and urinary protein electrophoresis showed pauci-immune ANCA GN with nephrotic proteinuria had obvious non-selective proteinuria. Conclusions: Pauci-immune ANCA GN with nephrotic proteinuria do not have more severe hypoalbuminemia, hypercoagulability or hyperlipidemia than patients without nephrotic proteinuria. Non-selective proteinuria might be the reason. However, pauci-immune ANCA GN with nephrotic proteinuria have more prevalent crescentic category in histopathology, higher incidence of AKI, gross hematuria and poorer renal prognosis despite of good sensitivity to therapy of proteinuria.